Tinjauan Hukum Islam Tentang Jual Beli Via Telepon dan Internet - Rasyidin Imran (Universitas Islam Negeri Imam Bonjol Padang, 2018)
Buying and selling or business in Islamic law includes muamalah category whose original law is permissible (except), except if there is a proposition that forbids it. Forbidden in the sale-purchase transaction is a transaction in which there are illicit elements such as usury, qharar (fraud), dharar (danger), jahalah (obscurity), zhalim (harming other people's rights) and coercion. In addition to the things mentioned, the goods or services that are commercialized are halal.The issue of buying and selling in the perspective of the Qur'an and hadith seems not to be seen from the type or model of the facilities used, but rather emphasizes moral principles such as honesty. Therefore, selling defective items without notifying the buyer is reproached. More than just honesty, the principle of likes and likes is emphasized. because in Islam, coercion in buying and selling transactions is prohibited. Thus, it can be said that as long as the sale and purchase transaction runs on these conditions and corridors, all forms of transactions are permitted, including via telephone and internet (or the like). this skill besides being based on the moral principles mentioned above, is also based on the aspects of the benefit it contains.